Phytochemical activities of Aspilia africana leaf using different extractants - Oko, Oluwatosin O. Kennedy; Agiang, Emmanuel Abekam (The Indian Journal of Animal Sciences, 2011)
Aspilia africana plant is used in herbal medicine for the perceived presence of some bioactive components in the leaves. Scientific reports suggest that different crude extracts of the plant contain specific bioactive constituents that could have varied effects on its biological activities. This study evaluated the phytochemical activities in the meal; aqueous, chloroform and ethanolic extracts of A. africana leaves. The anti-microbial activity of the four samples of A. africana were tested on nine micro-organisms of six bacteria and three fungal strains using the agar well diffussion technique. Results of the phytochemical screening and subsequent quantification revealed the presence of high amount of some bioactive compounds; saponins, tannins, alkaloids, flavonoids, terpenoid and phenol, but the absence of steroids (leaf meal and all extracts), phylobatannin (chloroform and ethanolic extracts) and cardiac glycoside (ethanolic extract) in the A. africana leaf products. Though the chloroform leaf extract had higher concentrations (P< 0.05) of these phytochemicals, significant (P< 0.05) improvements were observed in the chemical composition of the aqueous and ethanolic extracts. The anti-microbial activities observed indicated that biological activities were dependent on the types of extractants and the concentrations of principles present such as alkaloids and tannins. These activities were comparable to those obtained for ampicilin and gentamycin. The susceptibility of the microorganisms to the different A. africana leaf samples demonstrated its anti-bacterial and anti-fungal potentials and validated its use as an anti-microbial agent in ethnoveterinary medicine. Further investigations are required on their efficacies as phytobiotics in animal production.